Effect of soil compaction in the sub-humid cropping environment in Pakistan on uptake of NPK and grain yield in wheat (Triticum aestivum): I Compaction. - Ahmed, N.; Hassan, F.U.; Belford, Robert (Elsevier, 2009)
Soil compaction is a major cause of decrease in crop yield. The most serious cause of soil compaction is continuous ploughing at the same depth which affects bulk density, porosity and root proliferation, consequently affecting concentration and uptake of nutrients by plants. The effects of soil compaction on concentration and uptake of Nitrogen, Phosphorus and Potassium (NPK) by wheat were studied at the Agriculture Research Institute, Mingora, Pakistan in two separate experiments, conducted during 2002–2003 and repeated in 2003–2004. The treatments in each experiment consisted of four compaction levels arranged in a randomized complete block design replicated four times. Subsoil compaction affected soil bulk density and total porosity. With increasing compaction, bulk density increased in the range of 15–26% while total porosity decreased in the range of 15–27%. Compaction treatments significantly and progressively decreased concentration and uptake of NPK in both years of the experiments. Higher nutrient concentration and uptake was recorded during the second year as compared to first year, probably as a result of higher seasonal rainfall. Concentration of NPK showed reductions of 5–20%, 10–53% and 9–21%, respectively, due to the compaction treatments over control. The uptake of NPK decreased due to the compaction treatments in the range of 7–26%, 11–54% and 11–28%, respectively, over control. Compaction treatments decreased the dry matter accumulation in the range of 2–9% whereas grain yield showed a reduction of 5–48%. Inverse relationships between bulk density, and concentration and uptake of NPK, dry matter accumulation and grain yield were recorded. The implications of these findings for intensive agricultural systems in Pakistan and similar environments are discussed.